The Oral and Nasal Gateway Microbiomes: Salivaomics and Systemic Health at the Airway–Digestive Interface - Mark L. Cannon; John Peldyak; Paul R. Reynolds; Gustavo Ferrer (Microorganisms, 2026)
The oral cavity is a mucosal and mineralized interface shared by the digestive tract and the upper airway. This narrative review proposes the oral–nasal gateway microbiome as a clinically useful model for understanding oral, nasal, and systemic health. The model includes bacteria, fungi, archaea, protozoa, viruses, bacteriophages, microbial metabolites, and host-derived salivary components. Its gateway role is supported by anatomy, continuous salivation, periodontal vascular exposure, oral–gut microbial overlap, nitrate–nitrite–nitric oxide biology, oral and nasal airway interactions, maternal–child microbial transmission, and enrichment of oral organisms in selected distal diseases and tumors. Oral communities respond rapidly to diet, salivary flow, airway physiology, smoking and vaping, xerostomic medications, antibiotics, and antiseptic rinses, and these changes may influence the nasal microbiome. Published evidence summarizes bacterial pathobionts and protective commensals; Candida and other oral fungi; herpesviruses; papillomaviruses; bacteriophages; salivaomics; pregnancy and early-life prevention; probiotics; polyols; remineralization chemistry; environmental exposures; and tumor microbiology. As of manuscript preparation, SalivaDB catalogs 15,821 salivary biomarker entries across 201 diseases and 48 disease categories. The practical endpoint is not sterilization of the oral cavity but restoration of microbial homeostasis, salivary competence, airway stability, dietary balance, and biologically informed, timely prevention.